Effect of salinity on germination and early seedling growth of maize (Progressive Agriculture, 2017)
An incubation experiment was conducted at the Department of Soil Science, Patuakhali Science and Technology University during Rabi season 2015 to investigate the effects of different levels of salinity on germination and early seedling growth of maize. There were ten treatments consisting of different concentrations of salinity viz. 0, 20, 40, 80, 120, 160, 200, 240, 280 and 320 mM NaCl. The germination experiment was conducted in petri dish lined with a layer of cotton consisting ten ml of each test solution. Germination percentage gradually decreased with the increase of concentration of salt. Up to 80 mM concentration was found safe for maize seed germination. Salinity caused delay in germination.  Highest seedling height was found at 40 mM NaCl concentration (21.51 cm) and root length (23.61 cm) was found in 20 mM NaCl concentration. In 320 mM NaCl concentration roots were abnormal, deformed and twisted. The 0 to 80 mM NaCl concentration gave statistically similar shoot fresh weight. Compared to control treatment 20 mM NaCl concentration gave 0.55 % higher fresh weight and at 80 mM NaCl concentration shoot fresh weight reduced by only 6.9 %. The 80 mM NaCl concentration was found acceptable for germination and early seedling growth of maize.Progressive Agriculture 28 (1): 18-25, 2017